(Invited) Investigation of the Si/TiO2/Electrolyte Interface Using Operando Tender X-ray Photoelectron Spectroscopy. (13th April 2015) - Lichterman, Michael Frankston; Richter, Matthias Hermann; Hu, Shu; Crumlin, Ethan J; Axnanda, S; Favaro, Marco; Drisdell, Walter; Hussain, Z; Mayer, Thomas; Brunschwig, Bruce; Lewis, Nathan S.; Lewerenz, Hans Joachim; et al.
Abstract : Semiconductor-electrolyte interfaces allow for the creation of photoactive semiconductor systems that have band bending and other characteristics analogous to semiconductor-metal junctions (Schottky junctions). We demonstrate herein that XPS measurements can be obtained on a full three-electrode electrochemical system under potentiostatic control by use of tender X-rays to provide photoelectrons with sufficient kinetic energy to penetrate through a thin electrolyte overlayer on a portion of the working electrode. The response of the photoelectron binding energies to variations in applied voltage demonstrates that the XPS investigation works in an operando manner to elucidate the energetics of such interfaces.